Rhombencephalosynapsis: Fused cerebellum, confused geneticists. Issue 4 (22nd December 2018) - Aldinger, Kimberly A.; Dempsey, Jennifer C.; Tully, Hannah M.; Grout, Megan E.; Mehaffey, Michele G.; Dobyns, William B.; Doherty, Dan
Abstract : Rhombencephalosynapsis (RES) is a unique cerebellar malformation characterized by fusion of the cerebellar hemispheres with partial or complete absence of a recognizable cerebellar vermis. Subsets of patients also have other brain malformations such as midbrain fusion with aqueductal stenosis, characteristic craniofacial features (prominent forehead, flat midface, hypertelorism, ear abnormalities), and somatic malformations (heart, kidney, spine, and limb defects). Similar to known genetic brain malformations, the RES cerebellar malformation is highly stereotyped, yet no genetic causes have been identified. Here, we outline our current understanding of the genetic basis for RES, discuss limitations, and outline future approaches to identifying the causes of this fascinating brain malformation.